1983
DOI: 10.1016/s0022-5347(17)51764-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Partial Ureteric Obstruction in Newborn Rats. IV. Do the Morphological Effects Progress Continuously?

Abstract: Partial obstruction of the ureter was created in newborn rats, and its effects were studied after 1, 2, 3, 6 and 9 weeks--that is, until adult age. Within 1 week, a considerable hydronephrosis had appeared. Within 2 weeks, parenchymal weight was found slightly reduced (8 per cent) on the obstructed side, and, within 3 weeks, equivalently increased on the contralateral, intact side. After these points in time, there was no further deterioration. Histological examination revealed marked deformation of the papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 11 publications
4
21
0
Order By: Relevance
“…There was no con vincing evidence of any change with time. The hypertro phy was moderate, but comparable to what we observed with permanent obstruction: the contralateral weight was 9% above controls after 6 weeks [16], 6% after 9 weeks [17,18] and 13% after 1 year [ 19], Irreversibility is one explanation for persistence of con tralateral hypertrophy; its existence has, however, been debated. In normal rats with a normal, third transplant kidney, both absence [7,20] and presence [6,9] of reversal have been observed.…”
Section: Discussionsupporting
confidence: 84%
“…There was no con vincing evidence of any change with time. The hypertro phy was moderate, but comparable to what we observed with permanent obstruction: the contralateral weight was 9% above controls after 6 weeks [16], 6% after 9 weeks [17,18] and 13% after 1 year [ 19], Irreversibility is one explanation for persistence of con tralateral hypertrophy; its existence has, however, been debated. In normal rats with a normal, third transplant kidney, both absence [7,20] and presence [6,9] of reversal have been observed.…”
Section: Discussionsupporting
confidence: 84%
“…But many studies using the same model have revealed different results. Some differences such as fibrosis in the renal pelvis and deformation in the renal papilla have been reported in the second week of partial unilateral ureteral obstruction (Claesson et al, 1983). On the contrary, dilatation, local inflammatory response and degeneration in collective and corrugated tubules are not remarkable.…”
Section: Discussionmentioning
confidence: 98%
“…The disproportion between the immature and mature layers of the cortex is better explained by a delay in the postnatal differention. Such a disturbance would explain why, in chronic partial ureteric obstruc tion, the parenchymal weight is reduced only in rats obstructed neonatally [5,9] but not in rats obstructed at the age of 3-6 weeks [10-12].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why the parenchymal weight reduction, develop ing within 2 weeks after creation of ureteric obstruction in newborn rats, does not progress after that [5] and why this weight reduction is avoided only if the obstruction is released already within the first few days [6], The impor tance of the first obstructive period is supported by clin ical observations in children with hydronephrosis un dergoing surgical treatment; following pyeloplasty, the previously obstructed kidney grows but remains in the same weight 'channel' as before [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation